2005
DOI: 10.1016/j.cub.2005.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Lipid-Droplet Transport by the Perilipin Homolog LSD2

Abstract: LSD2 appears to represent a new class of regulators, a protein that transduces regulatory signals to a separable core motor machinery. In addition, the demonstration that LSD2 regulates both transport and lipid metabolism suggests a link between lipid-droplet motion and lipid homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
197
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(202 citation statements)
references
References 39 publications
5
197
0
Order By: Relevance
“…Equal amounts (0.2 g, wet weight) of mycelia were incubated (6 h) in 10 ml of water or water supplemented with 0.1% bean root exudate (25) or 1% cuticle. Mycelia were also incubated in minimal medium (MM, glucose 10 g/liter, NaNO 3 6 g/liter, KCl 0.52 g/liter, MgSO 4 ⅐7H 2 O 0.52 g/liter, KH 2 PO 4 0.25 g/liter) or in hemolymph of Manduca sexta.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equal amounts (0.2 g, wet weight) of mycelia were incubated (6 h) in 10 ml of water or water supplemented with 0.1% bean root exudate (25) or 1% cuticle. Mycelia were also incubated in minimal medium (MM, glucose 10 g/liter, NaNO 3 6 g/liter, KCl 0.52 g/liter, MgSO 4 ⅐7H 2 O 0.52 g/liter, KH 2 PO 4 0.25 g/liter) or in hemolymph of Manduca sexta.…”
Section: Methodsmentioning
confidence: 99%
“…3D) indicate that Mpl1 is not crucially involved in mediating the positioning of droplets in Metarhizium. This contrasts with Drosophila where perilipin regulates transportation of LDs (25). The pattern of LD distribution was also studied during formation of appressoria on locust hind wings.…”
Section: Loss Of Function Mutants Confirm That Mpl1 Plays Anmentioning
confidence: 99%
“…Dynein (Gross et al 2000;Bostrom et al 2005) and kinesin-1 (Shubeita et al 2008) (minusend and plus-end motors, respectively) were found to associate with LDs. In Drosophila melanogaster, a PAT protein homolog, LSD2, regulates bidirectional LD movement by coordinating opposite-polarity motor proteins (Welte et al 2005). Overexpression and deficiency of LSD2 leads to obese and lean flies, respectively, indicating that LSD2 is required for normal lipid storage (Gronke et al 2003).…”
Section: Lipid Droplet Motilitymentioning
confidence: 99%
“…On one side, inv is closely related in genome position, sequence and pattern of expression to engrailed (a segment polarity gene; Coleman et al, 1987). On the other side, Lsd-2 is related to the transportation of lipid particles along the microtubules and its regulation (Welte et al, 2005) as well as to lipid (Gronke et al, 2003) and triacylglycerol sequestering (Teixeira et al, 2003). In general, studies of the effect of Lsd-2 lack-of-function and gain-of-function mutations have shown that this gene is essential for an adjustment of the organismal lipid storage level.…”
Section: Body Size In Drosophilamentioning
confidence: 99%